Enhancing administrative efficiency in higher education with AI: a chatbot solution - Majorana, Cristina Doritta Brandão; Gonçalves, Renata Benigna; Neto , Fernando Luis Abegao; Camargo , Ricardo Zagallo (Review of Artificial Intelligence in Education, 2022)
<div class="min-h-[20px] text-message flex flex-col items-start gap-3 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" data-message-author-role="assistant" data-message-id="2ce592f7-d701-45c4-9900-feb6b0d749aa"> Objective: To alleviate high demand on the Stricto Sensu secretariat through a chatbot designed for various inquiries. Method: Utilized a qualitative approach, leveraging interviews for empirical analysis and Ishikawa diagrams for process mapping. Results: Demonstrated the chatbot’s capacity to streamline secretarial tasks, especially highlighted during pandemic-induced challenges. Practical Implications: The initiative offers a scalable model for enhancing administrative efficiency across higher education institutions, promoting interdisciplinary collaboration and technological integration. Conclusions: By improving response efficiency and reducing wait times for student requests, the chatbot exemplifies the transformative potential of AI in educational administration, suggesting a strategic direction for future technological adoptions in higher education.